KNOWLEDGE MANAGEMENT PROCESS & ITS ROLE UNDER HIGHER EDUCATION INSTITUTES - Ajim Shaikh; Vinod M. Charawande (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
This Paper presents systematic literature review onKnowledge management process & its role under higher education institutes. The main aim to study the knowledge management system under the education sector is to capture, store, share, & improve explicit knowledge for students, faculties & staff under universities with the help of modern technology. The intellectual assets under universities (e.g. faculties) gains or deliver the explicit knowledge through books, Internet, & Faculty Development Programs. The outcome of the questionnaires Session with the faculties & students clarify that Knowledge Management System Under universities could uplift the proficiency, effectiveness, & calibre of each individual member. The Knowledge Management cluster has sustained over the past few years, though the direction to implement or process explicit knowledge has not always been easier or manageable without the help of modern technology. Universities have significant possibilities to apply Knowledge Management System practices as mentioned above. The paper is based on a recent literatures study & case studies.